Ultramafic Rocks and Their Alteration Products From Northwestern Allaqi Province, Southeastern Desert, Egypt: Petrology, Mineralogy, and Geochemistry - Abdel-Rahman, A. M.; El-Desoky, H. M.; Shalaby, B. N. A.; Awad, H. A.; Ene, Antoaneta; Heikal, M. A.; El-Awny, H.; Fahmy, W.; Taalab, S. A.; Zakaly, Hesham M. H. (Frontiers in Earth Science, 2022)
The ophiolitic rocks, island arc metasediments and granitic rocks are encountered in the study Allaqi province. The present study concentrated on the ultramafic rocks and their various forms of hydrothermal alteration. Ophiolites commonly occur as dismembered rock sequences and have different types of hydrothermal alteration products. Ophiolites contain the essential type as serpentinites as well as talc carbonate rocks, listwaenites, and amphibolites along shear zones and faults. Listwaenite is one of the most significant rocks in this area because it contains gold. The whole serpentinite rocks are affected by regional metamorphosed to greenschist facies. Geochemically, Neoproterozoic serpentinites fall into SSZ ophiolites, Alpine type peridotite, formed in fore arc peridotite tectonic environment. Regarding, the listwaenite and talc carbonate rocks, revealed that trend to silica, carbonate, and talc. Listwaenites are classified into two types: carbonate rich listwaenite and silica rich listwaenites. Magnetite, chromite, galena, and gold are the most typical ores recorded in this research.